Larvacidal Activity of the Mulberry (Morus alba L.) Leaf Extract Against Larvae of Aedes aegypti - Muflikhah, Nina Difla (Institute of Topical Disease Universitas Airlangga, 2023)
Dengue Haemorrhagic Fever (DHF) is one of the major public health problems in Indonesia. As the population density increases, the number of sufferers increases. Aedes aegypti mosquitoes are vectors for the disease. The absence of drugs make the best prevention effort by eradicating mosquito nests, killing larvae and adult mosquitoes. Mulberry leaves (Morus alba L.) may be used as larvacides in the presence of chemical compounds of flavonoids and saponins that inhibit feeding and disrupt the process of insect metabolism. The purpose of this research has to determine the effect of mulberry leaf extract (Morus alba L.), to determine the larvicide effect of mulberry leaf extract (Morus alba L.) and to determine the concentration of mulberry leaf extract (Morus alba L.) which is optimal in killing third instar Aedes aegypti larvae. This research used Randomized Design Group (RDG) method with treatment consisted 4 concentrations (0.25%, 0.5%, 0.75%, and 1%), negative control and positive control (ABATE) with 6 repetitions. The results of probit analysis showed that LC50 values were 1.124% and LC90 was 4.413%. From the one way ANOVA test at each concentration of 0.25%, 0.5%, 0.75%, and 1%, the F count result is 208.331, the value was greater than F table which is 2.53 and the significant value is 0.000 (sig <0.05) then mulberry leaf extract (Morus alba L.) has a affected to eliminated of Aedes aegypti larvae. Conclusion from the results of the one way ANOVA test of mulberry leaf extract (Morus alba L.) was affected to eliminated third instar Aedes aegypti larvae